2014
DOI: 10.1128/cvi.00471-14
|View full text |Cite
|
Sign up to set email alerts
|

Stimulation of Innate Immunity byIn VivoCyclic di-GMP Synthesis Using Adenovirus

Abstract: The bacterial second messenger cyclic di-GMP (c-di-GMP) stimulates inflammation by initiating innate immune cell recruitment and triggering the release of proinflammatory cytokines and chemokines. These properties make c-di-GMP a promising candidate for use as a vaccine adjuvant, and numerous studies have demonstrated that administration of purified c-di-GMP with different antigens increases protection against infection in animal models. Here, we have developed a novel approach to produce c-di-GMP inside host … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(22 citation statements)
references
References 63 publications
1
21
0
Order By: Relevance
“…We previously demonstrated the feasibility of in vitro and in vivo production of c-di-GMP in mammalian cells by using Ad5 vectors to transduce DGCs (30). Our prior unpublished studies suggested that use of an alternative DGC, VCA0848, which has greater enzymatic activities, might generate a significantly elevated amount of c-di-GMP in vivo .…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…We previously demonstrated the feasibility of in vitro and in vivo production of c-di-GMP in mammalian cells by using Ad5 vectors to transduce DGCs (30). Our prior unpublished studies suggested that use of an alternative DGC, VCA0848, which has greater enzymatic activities, might generate a significantly elevated amount of c-di-GMP in vivo .…”
Section: Resultsmentioning
confidence: 99%
“…AdNull and AdGag were constructed as previously described (31, 32). AdVCA0848 was constructed similarly to AdVCA0956 as previously described (30). Briefly, the V. cholerae gene VCA0848 gene (GeneBank sequence: CP007635.1) was sub-cloned into pShuttle-CMV as previously described (33).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations